Agile approaches on large projects in large organizations - Hobbs, Brian; Petit, Yvan, 1958 November 24- (Project Management Institute, Inc., 2017)
Creativity and productivity, rapid adaptation to change, value for the customer -- these are just some of the advantages of implementing agile methods in project work. However, agile methods have been most widely and successfully undertaken in the context of small, collocated teams working on small software projects, known as the "agile sweet spot." In this monograph, Brian Hobbs and Yvan Petit explore the use and impact of agile outside of the agile sweet spot. Through a case study and survey questionnaire, they uncover research questions that have remained largely unexamined in the literature, on the project level as well as on the organizational level, namely: 1.) What challenges are encountered when applying agile approaches to large, multi-team software projects and what practices have been developed to alleviate these challenges? 2.) How does the context of large, complex organizations affect the adaptation and adoption of agile approaches and vice versa? An illuminating study of this emerging field, Agile Methods on Large Projects in Large Organizations opens the door to further investigation on the future role of project managers, the use of scaling frameworks at the program and portfolio levels, and the effects of DevOps, one of the recent trends in agile software development